Portofolio-Based Islamic Education Learning in the Discourse of Character Building at Al-Azhar Muhammadiyah Sukamenanti Junior High School - Sedihati Halawa (Ruhama : Islamic Education Journal, 2023)
The Portofolio-Based Learning Model emphasizes the consideration of the progress of the student learning process that is structured so that students are able to see the progress of each work. The use of the right learning model can encourage the growth of students' enjoyment of the lesson, grow and increase motivation in doing assignments, make it easier for students to understand the lesson so as to enable students to achieve good learning outcomes. There are various learning models that can be used by teachers, for example direct learning, cooperative learning, problem-based learning, learning based on 4 competencies, learning with a contextual approach, thorough learning, constructivism, and so on. The purpose of writing this thesis is to explain: (1) portfolio-based Islamic Religious Education Learning model in fostering the character of students at SMP Al-Azhar Muhammadiyah Sukamenanti; (2) the steps taken by the teacher in implementing portfolio-based Islamic Religious Education learning towards character building of students at SMP Al-Azhar Muhammadiyah Sukamenanti; (3) the advantages and disadvantages of portfolio-based learning models in character building of students at SMP Al-Azhar Muhammadiyah Sukamenanti for the 2020/2021 Academic Year.Based on the results of the research that the author conducted, several conclusions can be drawn which include: (1) Portfolio-based Islamic Religious Education Learning Model in fostering the character of students at Al-Azhar Muhammadiyah Sukamenanti Middle School in accordance with the 2013 curriculum, namely a learning model that involves more student activity in form of discussion; (2) the steps in the portfolio-based learning model: identifying existing problems, choosing a problem to study in class, collecting information related to the problem being studied, making class portfolios, presenting portfolios/hearings, reflecting on learning experiences; (3) the advantages of the portfolio-based learning model: motivating a sense of care or sensitivity to the community environment from the closest to national and even international problems, educating students to have the ability to reflect on their learning experiences, to have learning experiences from everything they have done; and the lack of a portfolio-based learning model: it takes a relatively long time, requires perseverance, patience and the skills of educators, requires a close communication network between students, educators, schools, families, communities, and government and private institutions or agencies.